Stability of percutaneously implanted markers for lung stereotactic radiotherapy. (6th September 2013) - Persson, Gitte F.; Josipovic, Mirjana; von der Recke, Peter; Aznar, Marianne C.; Juhler‐Nøttrup, Trine; Munck af Rosenschöld, Per; Korreman, Stine; Specht, and Lena
Abstract : The purpose of this study was to evaluate the stability of complex markers implanted into lung tumors throughout a course of stereotactic body radiotherapy (SBRT). Fifteen patients referred for lung SBRT were prospectively included. Radio‐opaque markers were implanted percutaneously, guided by computed tomography (CT). Deep inspiration breath‐hold CT scans (BHCT) were acquired at planning and on three treatment days. The treatment days' BHCTs were registered to the planning BHCT. Intraobserver uncertainty in both tumor and marker registration was determined. Deviations in the difference between tumor and marker‐based image registrations of the BHCT scans during treatment quantified the marker stability. Marker position deviation relative to tumor position of less than 2 mm in all three dimensions was considered acceptable for treatment delivery precision. Intra‐observer uncertainties for image registration in the left‐right (LR), anterior‐posterior (AP), craniocaudal (CC) directions and three‐dimensional vector (3D) were 0.9 mm, 0.9 mm, 1.0 mm, and 1.1 mm (SD) for tumor registration and 0.3 mm, 0. 5 mm, 0.7 mm, and 0.7 mm (SD) for marker registration. Mean 3D differences for tumor registrations on all days were significantly larger than for 3D marker registrations ( p   =   0.007 ) . Overall median differences between tumor and marker position were 0.0 mm (range ‐2.9 to 2.6 mm) in LR, 0.0 mm (‐1.8 to 1.5 mm) in AP, and ‐0.2 mm (‐2.6 to 2.8 mm) in CC directions. Four patients had deviations exceeding 2 mm in one or more registrations throughout the SBRT course. This is the first study to evaluate stability of complex markers implanted percutaneously into lung tumors for image guidance in SBRT. We conclude that the observed stability of marker position within the tumor indicates that complex markers can be used as surrogates for tumor position during a short course of SBRT as long as the uncertainties related to their position within the tumor are incorporated into the planning target volume. PACS number: 87.57.nj, 87.55.ne